(untitled) (Management and Connections Journal, 2023)
Telework, first adopted in private companies, has recently been implemented in public organizations. This review aims to systematize research interests and objects in telework in the Brazilian Public Administration – based on an inventory in the Capes Catalog of Theses and Dissertations – aiming at defining a research agenda and feedback from similar systems. It took place by the descriptor “telework” with filter in Applied Social Sciences/Public Administration. The results are, in their entirety, from research carried out in master’s courses, mostly in public universities. The analysis of methodological approaches reveals a predominance of qualitative procedures. Research at the federal level, in public educational institutions and from the Southeast region prevail, addressing the implementation of telework and its impacts, focusing on advantages, disadvantages, challenges and potential. A strong influence of the covid-19 pandemic on the interest in the topic is evident. There is a lack of research at the municipal level and in bodies of the Legislative Power.